PEMBERIAN EKSTRAK Bambusa vulgaris var DAN Musa paradisiaca TERHADAP PERTUMBUHAN Caesalpinia Sp - Reti Novianti; Deni Parlindungan; Ariefa Primairyani; Widia Gusti; Ika Saputri (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aimed to measure the effect of Bambusa vulgaris var and Musa paradisiaca extract on Kebiul (Caesalpinia sp) cuttings were compared with synthetic PGR (Rootone-F) and controls. This research was conducted for six weeks (March-April 2021). Kebiul is a traditional medicinal plant that used by Bengkulunese but mostly they only harvest from nature without cultivating the plant. Bamboo shoots (B. vulgaris var) and banana hump (M. paradisaca) extract are natural PGRs that are commonly used. The content of gibberellins in bamboo plays a role in breaking dormancy, while cytokinins in bananas play a role in increasing cell growth and development. The results showed that the treatment of B.vulgaris var and M.paradisaca extracts gave a good response to the number of growing , number of shoots, growth time, growth rate, and number of leaves. The giving of extracts of B.vulgaris var and M. paradisaca was able to accelerate the growth of kebiul cuttings.